2017
DOI: 10.1002/cphc.201700695
|View full text |Cite
|
Sign up to set email alerts
|

CaO‐Based CO2 Sorbents Effectively Stabilized by Metal Oxides

Abstract: Calcium looping (i.e., CO2 capture by CaO) is a promising second‐generation CO2 capture technology. CaO, derived from naturally occurring limestone, offers an inexpensive solution, but due to the harsh operating conditions of the process, limestone‐derived sorbents undergo a rapid capacity decay induced by the sintering of CaCO3. Here, we report a Pechini method to synthesize cyclically stable, CaO‐based CO2 sorbents with a high CO2 uptake capacity. The sorbents synthesized feature compositional homogeneity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
(33 reference statements)
1
23
0
Order By: Relevance
“…Indeed, deactivation in the range of 30-60% of the initial uptake has been reported 23,33,34 . Previous studies have attributed the decay in the CO2 uptake of MgO largely to sintering, however without providing experimental evidence 23,27,28 , assuming instead an analogy to the behavior of CaO-based sorbents 10,11,37,38 . Only recently, Zhao et al 31 provided evidence that the surface area and pore size of a NaNO3-promoted mesoporous MgO sorbent decreased after carbonation and subsequent regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, deactivation in the range of 30-60% of the initial uptake has been reported 23,33,34 . Previous studies have attributed the decay in the CO2 uptake of MgO largely to sintering, however without providing experimental evidence 23,27,28 , assuming instead an analogy to the behavior of CaO-based sorbents 10,11,37,38 . Only recently, Zhao et al 31 provided evidence that the surface area and pore size of a NaNO3-promoted mesoporous MgO sorbent decreased after carbonation and subsequent regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The effective incorporation of a stabilizer into a porous CaO structure relies on two key aspects: (i) its homogeneous distribution within the CaO matrix on a nanometer or even atomic level, and (ii) the minimization of its quantity to maintain a high fraction of CaO in the material. However, it is also worth noting that several reports have indicated that the presence of a stabilizer per se is not sufficient to realize sorbents featuring both cyclic stability and a high CO 2 uptake capacity 12 , 19 , 25 . Indeed, also the structure of CaO has to meet certain characteristics, such as being composed of small building blocks typically in the form of nanometer-sized particles/grains 11 , 20 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The in situ CO 2 capture is the core process for the research and development of this technology because it can effectively remove CO 2 , adjust the gas composition, and improve the quality of pyrolysis gas [6][7][8][9][10]. In order to enhance CO 2 adsorption capacity, CaO-based catalysts have been studied in biomass thermochemical conversion with in situ CO 2 capture [1][2][3][11][12][13][14][15][16]. Naeem et al [11] utilized the Pechini method to synthesize Al 2 O 3 -, MgO-, Y 2 O 3 -stabilized, and CaO-based CO 2 sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance CO 2 adsorption capacity, CaO-based catalysts have been studied in biomass thermochemical conversion with in situ CO 2 capture [1][2][3][11][12][13][14][15][16]. Naeem et al [11] utilized the Pechini method to synthesize Al 2 O 3 -, MgO-, Y 2 O 3 -stabilized, and CaO-based CO 2 sorbents. The experimental results exhibited high CO 2 uptake with improved cyclic stability and superior performance when compared to the performance of limestone-derived benchmark sorbent.…”
Section: Introductionmentioning
confidence: 99%